Etnobotanical Study of Medicinal Plants by the Community Pucung Village, Kismantoro District, Wonogiri Regency, Central Java - Nur Kholis Majid, Muhammad; Agustina, Ana; Lasekti Wicaksono, Rezky (Jurnal Biodjati, 2025)
Indonesia is known as a living laboratory because its forests host approximately 30,000 plant species, of which around 9,600 are medicinal. The benefits of natural medicines derived from plants have been empirically proven, encouraging communities to preserve them. The use of medicinal plants by communities reflects the relationship between humans and plants, known as ethnobotany. This relationship can show how the community of Pucung Village uses medicinal plants, the efforts and conservation status of the medicinal plant species found, and the community's perceptions of medicinal plants and the sustainability of local knowledge about their use for future generations. Using an ethnobotanical approach, this study focuses on local wisdom as the foundation for preserving knowledge of medicinal plants in Pucung Village. The data collection methods used were purposive sampling and snowball sampling. Using these techniques, 18 informants were identified. Based on the interview results, 56 plant types from 30 families were identified, with turmeric (100%) being the most frequently used. The plant part with the highest percentage was leaves (45.16%). The most dominant processing method was boiling (37.70%). The primary source of plant acquisition was cultivation activities (49.30%). The most common plant habit was herbaceous (37%). There are 24 medicinal plant species classified as least concern, 9 as data deficient, and 23 as not evaluated. Efforts to sustain local knowledge include direct practice and the transmission of knowledge through oral communication. Nine informants tend to use medicinal plants to maintain physical health, while nine others tend to prefer using medicinal plants first.